PENGARUH KOMPETENSI SDM DAN SISTEM AKUNTANSI KEUANGAN DAERAH TERHADAP KUALITAS LAPORAN KEUANGAN DAERAH - Abdul Rahman; Ayudhini Azzahra Permatasari (Magister Administrasi Publik, FISIP, 2021)
The purpose of this article is to determine the impact of human resource skills and financial accounting systems on the quality of regional financial statements. Using quantitative methods for accounting or financial personnel management at government offices in Buleleng regional, this study shows that human resource literacy and the financial system have a positive and significant impact on the quality of regional financial systems reported. Thus, the results of this study indicate the need to increase human resources for financial management in the regions and the financial accounting system in accordance with established standards.